Peran Strategi Marketing Mix Dalam Mempengaruhi Pilihan Perguruan Tinggi Swasta di Tangerang Raya Dengan Pendekatan Penelitian Kualitatif - Paulus Yulius Fanggidae; Antonius Juniarto (Akmenika: Jurnal Akuntansi dan Manajemen, 2023)
Providing a variety of facilities and infrastructure as well as engaging programs to support the process of "delivery" of educational services to their learning citizens is one of the challenges facing today's higher education institutions. This allows them to provide the best service possible during "service encounters," but it also necessitates that the executors be careful and make the appropriate policy decisions. Related to this, in this study the researcher conducted interviews with informants/informants who were high school students in the Greater Tangerang Region to obtain primary data which was then processed qualitatively using the case study approach "Marketing Mix Strategy 7P" (Product, Price, Place, Promotion, People, Process and Physical Evidence) and the Decision to Choose a Private Higher Education in Tangerang Raya. This research is expected to enrich the literature on the development of service marketing management science.to enrich the literature on the development of service marketing management science.